Combinational effect of resveratrol and atorvastatin on isoproterenol-induced cardiac hypertrophy in rats - Songjukta Chakraborty; Mukta Pujani; Syed Ehtaishamul Haque (Wolters Kluwer Medknow Publications, 2015)
Introduction: Resveratrol is a natural polyphenol present mainly in grapes. It has been shown to offer strong cardio protection in animal models due to its ability to correct lipid peroxidation and maintain antioxidants level. Atorvastatin, a HMG-CoA reductase inhibitor, lowers cholesterol level and is commonly prescribed to heart patients. Our aim in this study was to see the combination effect of these two drugs against Isoproterenol-induced cardiac hypertrophy in rats. Materials and Methods: Wister Albino rats were treated with resveratrol (20 mg/kg/day, p.o), atorvastatin (20 mg/kg/day, p.o) and in combination (resveratrol [10 mg/kg/day, p.o] + atorvastatin [10 mg/kg/day, p.o]) for a period of 25 days and from 15 th till 25 th day Isoproterenol (5 mg/kg/day, s.c) was co-administered to rats to induce cardiac hypertrophy. Results: A significant increase in creatine kinase, lactate dehydrogenase, aspartate transaminase and lipid peroxidation with the significant decrease in reduced glutathione, superoxide dismutase and catalase were observed in Isoproterenol treated rats. Resveratrol, atorvastatin and their combination significantly reversed the effect. The histopathological studies and myocardial infarct size evaluation also confirmed the protection. Conclusion: Comparing the data we came to this conclusion that atorvastatin although showed the protection along all the parameters, the extent of protection offered by resveratrol alone and in combination were more effective. Hence, it can be concluded that resveratrol, an herbal nutritional supplement, alone and in combination is better against cardiac hypertrophy.